ANALISA KONTRIBUSI PEMBIAYAAN MUSYARAKAH, MURABAHAH DAN IJARAH TERHADAP PROFITABILITAS (ROE) PADA BANK BNI SYARIAH - Hariyani, Diyah Santi (Fakultas Ekonomi Universitas Wisnuwardhana, 2016)
The objective of the research is to analyze empirical data aboutthe influence of musyarakah, murabahah and ijarah on profitability (ROE)The study uses causal relation quantitative research. Sample of the researchwas taken from Bank BNI Syariah’s financial statements per month in 2012-2014. Data collection techniques used are literature study and documentation.Secondary data retrieved from the data of Bank BNI Syariah’s financialstatements which can be accessed through the official website of BankIndonesia, www.bi.go.id. The statistical method in this research is multipleregressiontest.The statistical results shows that Musyarakah, murabahah and ijarahsignificant effect on profitability (ROE) simultaneously.Keywords: musyarakah, murabahah, ijarah, profitability (ROE)